1997
DOI: 10.1001/archpsyc.1997.01830160092012
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography Measurement of Cerebral Metabolic Correlates of Tryptophan Depletion—Induced Depressive Relapse

Abstract: Specific brain regions, including the middle frontal gyrus, thalamus, and orbitofrontal cortex, may mediate the symptoms of patients with major depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
145
1
4

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(164 citation statements)
references
References 75 publications
14
145
1
4
Order By: Relevance
“…For example, studies that examined abnormalities during a Major Depressive Episode and after various forms of treatment report normalization of orbitofrontal and anterior cingulate abnormalities with treatment (Baxter Jr et al, 1989;Bench et al, 1995;Brody et al, 1999;Buchsbaum et al, 1997;Mayberg et al, 2000Mayberg et al, , 2002. Indeed, Bremner et al (1997) found that depressed patients who were 6 weeks into a course of antidepressant treatment exhibited decreases in glucose metabolic rates in the orbitofrontal cortex and thalamus after a tryptophan-depletion-induced acute relapse compared to patients without depressive symptoms. A comparable pattern of abnormality in the orbitofrontal cortical region is seen in refractory depressed patients (Mayberg et al, 1997) and in patients with depression associated with neurological disorders (Bromfield et al, 1992;Mayberg et al, 1990Mayberg et al, , 1992.…”
Section: Orbitofrontal Cortex In Mdd With Bpd Compared To Mddmentioning
confidence: 99%
“…For example, studies that examined abnormalities during a Major Depressive Episode and after various forms of treatment report normalization of orbitofrontal and anterior cingulate abnormalities with treatment (Baxter Jr et al, 1989;Bench et al, 1995;Brody et al, 1999;Buchsbaum et al, 1997;Mayberg et al, 2000Mayberg et al, , 2002. Indeed, Bremner et al (1997) found that depressed patients who were 6 weeks into a course of antidepressant treatment exhibited decreases in glucose metabolic rates in the orbitofrontal cortex and thalamus after a tryptophan-depletion-induced acute relapse compared to patients without depressive symptoms. A comparable pattern of abnormality in the orbitofrontal cortical region is seen in refractory depressed patients (Mayberg et al, 1997) and in patients with depression associated with neurological disorders (Bromfield et al, 1992;Mayberg et al, 1990Mayberg et al, , 1992.…”
Section: Orbitofrontal Cortex In Mdd With Bpd Compared To Mddmentioning
confidence: 99%
“…Only change scores of the HRSD and plasma Trp levels were available in the study by Bremner et al (1997). These patients could therefore not be included in linear regression analyses.…”
Section: Missing Datamentioning
confidence: 99%
“…In Spillman et al (2001), , and Bremner et al(1997), a clinically significant recurrence in depressive symptoms after ATD (i.e. responder to ATD: depressive 'relapse') was explicitly defined.…”
Section: Computation Of Statistically Comparable Mood Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, clinical evidence indicates that reduction of brain 5-HT levels, induced by a dietary depletion of L-tryptophan, can reverse the antidepressant action of selective 5-HT reuptake inhibitors (SSRI), monoamine oxidase inhibitors (MAOIs), and the a 2 -adrenoceptor antagonist mirtazapine (Bremner et al, 1997;Nishizawa et al, 1997;Moreno et al, 2000). Preclinical studies show that antidepressant treatments increase 5-HT neurotransmission with a time course that is consistent with their delayed therapeutic effect.…”
Section: Introductionmentioning
confidence: 99%